Platypnea-Orthodeoxia Syndrome after SARS-CoV-2 interstitial pneumonia: an overview and an update on our patient - Zanoni, Nicola; Longo, Chiara; Frizzelli, Annalisa; Longo, Francesco; Accogli, Rocco; Chetta, Alfredo Antonio (Acta Biomedica Atenei Parmensis, 2022)
Platypnea-Orthodeoxia Syndrome (POS) is a clinical entity defined as positional dyspnoea (platypnea) and arterial desaturation (orthodeoxia) that occurs when sitting or standing up and usually resolves by lying down. Up to April 25th 2021, eleven cases of POS after SARS-CoV-2 pneumonia have been reported on Pubmed. Accordingly, SARS-CoV-2 infection may be considered as an emergent cause of POS due to an increase in ventilation/perfusion (V/Q) mismatch. In this article we provide an update on the patient with POS after fibrotic evolution of SARS-CoV-2 interstitial pneumonia, which we previously reported and we discuss the case reports of POS due to SARS-CoV-2 infection.